2012
DOI: 10.1089/ees.2011.0229
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of PM10 Emission Sources for Priority Regulation in Urban Air Quality Management Using a New Coupled MM5-CAMx-PSAT Modeling Approach

Abstract: In this study, a new method was proposed to systematically identify the local PM 10 emission sources for priority regulation in urban air quality management through a coupled MM5-CAMx-PSAT modeling system. Parameters of emission source contribution ratio (ESCR) and normalized local ESCR were introduced to reflect the source contribution in terms of its total emission amount and per unit emission amount, and were used for identifying the emission sources for priority regulation. The proposed method was then app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In terms of examining the response of atmospheric pollutant concentration to perturbations in pollutant emission rate, a number of approaches have been proposed in the past years by using various models [4,11,16,17]. Particularly, a technique named particulate matter source apportionment technology (PSAT) [18] has been implemented in CAMx to provide source apportionment for primary and secondary particulate matter (PM) species according to emission source categories and their geographic locations [19]. This technique is useful for identifying emission sources that significantly contribute to gaseous or PM pollution.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of examining the response of atmospheric pollutant concentration to perturbations in pollutant emission rate, a number of approaches have been proposed in the past years by using various models [4,11,16,17]. Particularly, a technique named particulate matter source apportionment technology (PSAT) [18] has been implemented in CAMx to provide source apportionment for primary and secondary particulate matter (PM) species according to emission source categories and their geographic locations [19]. This technique is useful for identifying emission sources that significantly contribute to gaseous or PM pollution.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate whether the SO 2 + NO 2 reactions in aerosol water could help better predict the enhanced sulfate formation during haze periods in the Yangtze River Delta (YRD) region, we implemented a parameterized SO 2 +NO 2 reactive uptake mechanism in the Comprehensive Air Quality Model with Extensions (CAMx), which is a widely used air quality model in China (e.g., Wang et al, 2009;Huang et al, 2012;Li et al, 2013Li et al, , 2015Jia et al, 2017). Our parameterization specifically incorporated RH and aerosol pH dependencies derived from measurement data during the 2015 Beijing haze event (Wang et al, 2016).…”
mentioning
confidence: 99%
“…Chatani et al (2011) developed a framework for a high-resolution, three-dimensional regional air quality simulation; their suspended PM prediction in Japan also showed under-predictions by ƀ37% to ƀ61% NMB, differing by seasons. To our knowledge, most modeling studies in the East Asia region showed under-predictions compared to the observations (Koo et al, 2008(Koo et al, , 2012Shimadera et al, 2009;Huang et al, 2012;In and Kim, 2010;Li et al, 2013;Chatani et al, 2011. One of the main reasons for underestimations in the aerosol simulation of PM10 in particular is the uncertainty of emissions.…”
Section: Introductionmentioning
confidence: 94%